Fathers and sons in Athens : ideology and society in the era of the Peloponnesian war - Strauss, Barry S. (Routledge, 1993)
As history's first democracy, classical Athens invited political discourse. The Athenians, however could not completely separate the politicals from the private sphere; indeed father-son conflict, from patricide to murdering one's son, was a major public as well as a private theme. In a fascinating historical reappraisal, the author explores the consequences, for Athens and us, of the powerful influence of familial ideology on politics.